Thymidylate synthase mRNA levels in plasma and tumor as potential predictive biomarkers for raltitrexed sensitivity in gastric cancer - Shen, Jie; Wang, Hao; Wei, Jia; Yu, Lixia; Xie, Li; Qian, Xiaoping; Zou, Zhengyun; Liu, Baorui; Guan, Wenxian (International journal of cancer, 2012)
Different chemotherapeutic agents currently available are effective only in certain subsets of patients. Predictive biomarkers will be helpful in choosing those agents and can improve the clinical efficiency by a more personalized chemotherapeutic approach. Raltitrexed is a novel water‐soluble quinazoline folate analogue and can improve the efficiency of gastric cancer treatment, but its predictive biomarker remains unclear. The aim of our study was to investigate the role of plasma and tumor thymidylate synthase (TS) mRNA levels as predictive biomarkers for raltitrexed in gastric cancer. In total, 125 freshly removed gastric tumor specimens and corresponding blood samples before surgery were collected. Raltitrexed sensitivity was determined by histoculture drug response assay procedures. TS mRNA levels in tumor and plasma were determined by quantitative reverse transcription polymerase chain reaction. Plasma TS mRNA level in cancer patients was significantly higher than in healthy subjects (p = 0.009) and was significantly correlated with TS mRNA level in tumor tissues (r = 0.665, p < 0.001). Tumor and plasma TS mRNA expression levels were significantly lower in raltitrexed‐sensitive group than in resistant group (p = 0.007 and 0.013, respectively). The sensitivity and accuracy of raltitrexed sensitivity prediction based on plasma TS mRNA levels were 82 and 60%, respectively, whereas the prediction based on tumor TS mRNA reached 70% sensitivity and 68% accuracy. These results indicate that TS mRNA level in plasma can mirror tumor TS mRNA level, and both of them can be used to predict raltitrexed sensitivity in gastric cancer.